PEMBERDAYAAN MASYARAKAT PETANI DALAM SWADAYA PUPUK KOMPOS BERBASIS KKN PPM - Triatmanto, Mutaqin, Totok Heru Trimaryadi, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
Community development learning activities for lecturer and studentsis a medium to contribute to the settlement of the problems in society. Thepurpose of this proram is: First, to be able to empower farming communitiesthrough a community initiative compost manure management to be used asorganic compost. Second, introducing appropriate technology composter forthe farmers as a tool for the process of making compost from cow manureinto organic fertilizer that is efficient and profitable.The method is applied in the framework of empowerment of the targetgroup through observation, interviews, documentation, education, training,practice, coaching, and monitoring of programs. To be in the implementationof these activities can work well, before the student falls on theground, first given a briefing on the program material that will apply to thetarget group .The results of the activities of this program are: (1) society has beenable to target the group of self-sufficient through the compost cow manuremanagement used as organic compost; (2) the target group has to know, canuse and take advantage of appropriate technology in the composter compostingprocess cow manure into organic fertilizer more efficiently and profitably.The implications of this program can serve as a model of communityempowerment in a self-sufficient farm compost compost to meet internalneeds, and can even be used as a productive economic activity.Keywords: community development, farming community, ability providecompost, animal waste